Biochar remediation of PFOA contaminated soil decreased the microbial network complexity. Issue 1 (February 2023) - Sun, Tao; Wang, Fenghua; Xie, Yangyang; Liu, Xin; Yu, Hui; Lv, Ming; Zhang, Yanhui; Xu, Yuxin
Abstract: Poly- and perfluoroalkyl substances (PFAS) are ubiquitous in the environment and have raised global concern. However, little is known about the microbial response to biochar remediation of PFAS contaminated soil. An indoor experiment was conducted to investigate how microbial community changed when exposed to perfluorooctanoic acid (PFOA) pollution (1 mg/kg) and 3% (w/w) biochar amendment. Results showed that PFOA contamination decreased bacteria diversity and altered microbial composition. Phylum Actinobacteria and genera Gaiella, Blastococcus, Solirubrobacter, and Knoellia were the biomarkers in the PFOA treatments. PFOA pollution decreased the interaction between bacterial genera compared with the control group. PICRUST predictions showed that the C cycling functional genes of coxSML and malZ, N cycling genes of ureC, nirB, nasAB and nxrAB, P cycling genes of pstABC and ugpQ, genes dehH and dhaA encoding dehalogenase were enhanced, phoR and phnP were reduced by PFOA contamination. Biochar remediation restored the bacterial community structure and function to the control level, however, the interaction between bacterial genera was significantly decreased compared with uncontaminated level, illustrated as the reduced number of edges (from 538 to 245), network average degree (from 22 to 10), network density (from 0.477 to 0.217), the clustering coefficients (from 0.727 to 0.534) and the increased average path length (from 1.752 to 2.322). Our study found for the first time the decreased microbial interaction induced by biochar remediation of PFOA contaminated soil and provided a deeper insight into the response of microbial interaction to biochar amendment of recalcitrant compounds-PFAS contaminated soil. Highlights: PFOA contamination reduced diversity indices of soil bacterial community. PFOA decreased soil bacterial community network complexity. PFOA altered soil microbial C, N and P cycling functional genes. Biochar remediation restored bacterial community composition and function in PFOA-contaminated soil. Biochar amendment significantly reduced bacterial community network stability.